Assessing the contribution of vegetation variation to streamflow variation in the Lancang River Basin, China - Liu, Yuan; Chen, Weiqiang; Li, Ling; Huang, Junchang; Wang, Xianglong; Guo, Yulong; Ji, Guangxing (Frontiers in Ecology and Evolution, 2023)
Lancang River Basin (LCRB) is the largest international river in Southeast Asia, its streamflow change may lead to disputes between countries to a certain extent. Therefore, it is of great significance to quantitatively calculate the impact of different factors on streamflow in LCRB. Firstly, the functional relationship between Budyko parameter (w) and Normalized Difference Vegetation Index (NDVI) was calculated for constructing a modified Budyko formula. Finally, we quantitatively estimated the influence of different factors on streamflow variation in the LCRB using the modified Budyko formula and elastic coefficient method. The conclusions showed that: 1) The sudden change year of streamflow at Yunjinghong hydrological station is 2005. 2) Budyko parameter (ω) has a good linear functional relation with NDVI in the LCRB (P<0.05). 3) Vegetation variation played the largest driving force for streamflow variation in the LCRB, accounting for 34.47%. The contribution rate of precipitation, reference evaporation and anthropogenic activities on runoff depth variation from 1982 to 2015 are 16.83%，17.61% and 31.09%, respectively.